STUDI FARMAKOVIGILAN OBAT ANTIHIPERTENSI PADA PASIEN HIPERTENSI RAWAT JALAN DI DR. A. DADI TJOKRODIPO BANDAR LAMPUNG PERIODE OKTOBER–NOVEMBER 2021 - Lilik Koernia Wahidah; Novita Tri Wahyuni; Dion Yongtama (JFL : Jurnal Farmasi Lampung, 2022)
Hypertension, also known as high blood pressure, is systolic pressure140 and diastolic pressure 80 mmHg. The more blood pressure is pumped by the heart and the narrower the arteries, the higher the blood pressure. This study aims to determine the occurrence of adverse drug reactions in hypertensive patients in RSD DR. A. Dadi Tjokrodipo Bandar Lampung. This research is a descriptive research with total sampling method. Collecting data by looking at the patient's medical record data. The results showed that the female sex was more dominant in suffering from hypertension, namely 20 female patients (62.5%) and 12 male patients (37.5%). The highest age characteristics were found in the age range of 46-55 years as many as 14 patients (43.75%). The most characteristic of hypertension was in the case of stage 2 hypertension with a total of 17 patients (53.12%). The highest pattern of drug use was amlodipine (37.5%). The incidence of drug interactions was 10 cases (31.25%) with minor severity. The highest incidence of ADR was in the "moderately probable" 1-4 with a total of 15 cases (46.87%). Keywords: ADR, hypertension, drug interactions, antihypertensive drugs